Gene‐Centric Metagenome Analysis Reveals Gene Clusters for Carbon Monoxide Conversion and Validates Isolation of a Clostridial Acetogen for C2 Chemical Production. Issue 6 (20th May 2019) - Kang, Hyunsoo; Park, Byeonghyeok; Bolo, Nicole R.; Pathiraja, Duleepa; Park, Shinyoung; Cha, Minseok; Choi, In‐G.; Chang, In S.
Abstract : Syngas fermentation is largely dependent on acetogens that occur in various anaerobic environmental samples including soil, sediment, and feces. Here the authors report the metagenomic isolation of acetogens for C2 chemical production from syngas. Screening acetogens for C2 chemical production typically involves detecting the presence of the Wood‐Ljungdahl Pathway for carbon monoxide conversion. The authors collect samples from river‐bed sediments potentially having conditions suitable for carbon monoxide‐converting anaerobes, and enrich the samples under carbon monoxide selection pressure. Changes in the microbial community during the experimental procedure are investigated using both amplicon and shotgun metagenome sequencing. Combined next‐generation sequencing techniques enabl in situ tracking of the major acetogenic bacterial group and lead to the discovery of a 16 kb of gene cluster for WLP. The authors isolat an acetogenic clostridial strain from the enrichment culture (strain H21‐9). The functional activity of H21‐9 is confirmed by its high level of production of C2 chemicals from carbon monoxide (77.4 mM acetate and 2.5 mM of ethanol). This approach of incorporating experimental enrichment with metagenomic analysis can facilitate the discovery of novel strains from environmental habitats by tracking target strains during the screening process, combined with validation of their functional activity. Abstract : The changes in the microbial community during the experimental procedure from river‐bed sediments to strain isolation are investigated using both amplicon and shotgun metagenome sequencing. DNA samples obtained from river‐bed sediment, enrichment culture, and isolated strain enable in situ tracking of the major acetogenic bacterial group and lead to the discovery of a 16 kb gene cluster for WLP, which is also confirmed in isolated strain H21‐9. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org.